(untitled) (Journal of Engineering, 2024)
Reactive powder concrete is an attractive new concrete technology for structural design applications. The technology has been used for different structures with several advantages. Strengthening and retrofitting structures using FRP has grown rapidly in the last decades to upgrade structures because of the gradual material degradation over time. The technique was applied mainly for conventional normal and high-strength concrete and steel. This study is conducted to study the performance of bonding interface among reactive powder concrete substrate and CFRP sheets using different parameters, including bond length, bond width, and bond–slip relations. Concrete prisms with dimensions of (25 x 25 x 75 mm) were adopted in the experimental program. Five groups of three specimens were tested using a single-lap shear test setup, and pull-out loading was applied for testing the specimens. Test results indicated significant bonding properties compared to the normal concrete.